2022
DOI: 10.3389/fimmu.2022.978435
|View full text |Cite
|
Sign up to set email alerts
|

Increased CEACAM1 expression on peripheral blood neutrophils in patients with rheumatoid arthritis

Abstract: Altered expression of adhesion molecules in immune cells has been demonstrated in rheumatoid arthritis (RA). Carcinoembryonic–antigen–related cell–adhesion molecule 1 (CEACAM1) is an adhesion molecule that acts as a coinhibitory receptor in the immune system. We investigated the role of CEACAM1 in immune cell subsets of patients with RA. Peripheral blood was obtained from 37 patients with RA and 20 healthy controls (HC). The expression of CEACAM1 and T–cell immunoglobulin mucin domain molecule (TIM) –3 on peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…CEACAM1 has been shown to be upregulated in in ammatory responses [16]. Indeed, we previously reported the increased expression levels of CEACAM1 in neutrophils isolated from patients with active RA [5]. In rheumatoid neutrophils, CEACAM1 expression could be induced by in ammatory cytokines, including TNF-α, an essential cytokine in the pathogenesis of RA [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…CEACAM1 has been shown to be upregulated in in ammatory responses [16]. Indeed, we previously reported the increased expression levels of CEACAM1 in neutrophils isolated from patients with active RA [5]. In rheumatoid neutrophils, CEACAM1 expression could be induced by in ammatory cytokines, including TNF-α, an essential cytokine in the pathogenesis of RA [17].…”
Section: Discussionmentioning
confidence: 93%
“…In the rheumatoid synovium, neutrophils in ltrating synovial membranes or uids play an important role in the pathogenesis of RA [4]. We previously reported that CEACAM1 is selectively expressed in neutrophils not in T cells or monocytes, upregulated in peripheral blood neutrophils isolated from patients with active RA [5]. This observation suggests that in ammatory stimuli induce upregulation of the CEACAM1 gene on neutrophils in patients with active RA.…”
Section: Introductionmentioning
confidence: 98%
“…Matsumoto et al reported that CEA-CAM1 was exclusively expressed on peripheral blood neutrophils in RA patients. In addition, the expression levels of CEACAM1 in RA neutrophils were associated with rheumatoid inflammation [25].…”
Section: Andandmentioning
confidence: 99%
“…,西森 克彦 1) ,水野 景太2) 前島 裕子1) ,下村 健寿1) ① 確率論では p MI = exp(−MI) , MI = −log(p MI ) が成立する。② 統計学では,サンプルサイズを N とすると, p N・MI = exp(−N・MI) , MI = −log(p N・MI ) /N が成立する。 2) 確率変数分布が既知の場合,フィッシャー正 確確率 P F について,③ MI = −log(P F ) /N が漸近 的に成立する。 以上 ① -③ は情報理論と確率統計学の統合を導 く新定理であり,両体系の手法を同時に適用可能と する。この定理を応用することで,高次元確率変数 間の MI と p 値の高精度定量に基づく,ab initio 遺 伝子軌道法を開発することができた 1 。 【文献】 1. Mori, T., et al Influential force : from Higgs to the novel immune checkpoint KYNU.…”
unclassified